The Politics of Economic Policy Reform in Developing Countries - Adams, Richard H., Jr. (World Bank, Washington, DC, 2014)
Because of politics, some economic policy reforms are adopted and pursued in the developing world, and others are delayed, and resisted. Economic reform is inherently a political act: It changes the distribution of benefits in society, benefiting some social groups, and hurting others. Social groups may oppose reform because of doubts about its benefits, or because they know it will harm their economic interests. The author shows how three types of reform - currency devaluation, the privatization of state enterprises, and the elimination of consumer (food) subsidies - affect the utility of nine different social groups (including international financial institutions). When governments try to privatize state-owned enterprises, for example, more social groups with greater political weight are likely to be disadvantaged than helped. Urban workers, urban bureaucrats, urban students, and the urban poor, are likely to "lose out" and will strongly oppose privatization. But the ruling elite, and urban politicians are also likely to at least partly resist privatization, fearing that such reform will reduce their economic "rents". More social groups, and power points thus oppose privatization than favor it, so this policy reform is likely to be delayed, or not implemented at all. However, social groups do not possess an absolute veto over economic reform, and policy reform can (and often does) occur, despite the opposition of certain social groups. It depends on the aggregate political weight of the groups opposing reform. For example, as the author shows, five social groups, either wholly or partly, oppose eliminating consumer (food) subsidies, but the combined weight of those groups is only roughly equal to the political weight of the four social groups - international financial institutions, the ruling elite, urban politicians, and urban capitalists - that favor this reform. Politically, consumer subsidies can be eliminated, or reduced, if the right kind of concern is shown for opposing social groups.